Effect of time of measurement on central corneal thickness in a sample of young myopes - Bariah Mohd Ali; Nur Fadhlina Junus (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to determine the effect of time of measurement on central corneal thickness in young myopes. Seventy healthy myopic subjects (non contact lens wearers) were involved in this study with mean age of 22.43 ± 1.76 years. Subjective refraction was determined using cross-cylinder technique, corneal curvature was measured using keratometer (Shin-Nippon) and central corneal thickness (CCT) was determined using specular microscope (Topcon SP-3000P). The CCT was measured in the morning (between 8 to 11 am) and in the afternoon (between 2 to 5 pm). The results showed that the mean of refraction for all subjects was -2.59 ± 1.85 DS and mean of cornea curvature was 7.74 ± 0.25 mm. Mean CCT in the morning was 517 ± 37 μm and 516 ± 36 μm in the afternon. Statistical analysis showed no significant difference between both measurements (T = 1.713 and P = 0.091). Correlation analysis showed insignificant correlation between CCT and refractive error (r = -0.078, p > 0.05) and CCT with corneal curvature in the horizontal meridian (r = 0.014, p > 0.05) and at vertical meridian (r = 0.029, p > 0.05). This study concluded that there is no significant effect of time of measurement on CCT in young myopes.